Plant Diversity of the Poaceae Tribe on Teletubbies Hill, Bumiaji Village, Batu City, East Java - Alieffia Dzalfani Kurnia Andani; Lisa Septiana; Ratna Puspitasari; Silvya Rosa Fadilla; Siti Ulfatun Nadliroh; Indra Fardhani (Postgraduate, University of Mataram, 2023)
Poaceae is an organism that can live and develop, generally found in tropical areas or areas with air temperature with sufficient rainfall to form grasslands. Poaceae have an important role as a barrier to erosion at the foot of the cliff. This study aims to determine the diversity of plants in the Poaceae family. The research was conducted by descriptive observation with observation techniques. The specimen collection method was roaming which was carried out in the Teletubbies Hill area, Bumiaji Village, Batu City, East Java. In collecting specimens, abiotic data were also collected as environmental parameters in the form of rainfall, number of rainy months, average daily temperature, and height above sea level to support the identification process. Based on the observation results, 6 species of the Poaceae family were found. The species found were Sporobolus indicus, Imperata cylindrical, Digitaria ciliaris, Lepetochloa, Bothriochloa ischaemum and Eragrostis unioloides.